2019
DOI: 10.1073/pnas.1811259115
|View full text |Cite
|
Sign up to set email alerts
|

Risk-taking bias in human decision-making is encoded via a right–left brain push–pull system

Abstract: SignificanceBiases and fallacies can nudge humans in one direction or another as they make decisions. During gambling, bias is often generated by internal factors, including individual preferences, past experience, or emotions, and can move a person toward or away from risky behavior. The neural mechanisms responsible for generating internal bias are largely unknown, limiting the treatment of patients with neurological diseases that impair decision-making. We applied mathematical modeling techniques and high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 61 publications
3
24
1
Order By: Relevance
“…RRA and Potential Implications. RRA in the OFC is consistent with many previous studies investigating the function of the OFC (36)(37)(38)(39)(40)(41)(42), yet those studies rarely acknowledge or discuss this observation (43,44).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…RRA and Potential Implications. RRA in the OFC is consistent with many previous studies investigating the function of the OFC (36)(37)(38)(39)(40)(41)(42), yet those studies rarely acknowledge or discuss this observation (43,44).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have suggested that lateralization in the OFC could be linked to valence processing (13), interpreted in an approach/avoidance framework (44) or in an exploration/exploitation framework (39). Yet our Neurosynth metaanalysis suggested that value-guided and motivational processes might be more supported by the left lOFC, while the right lOFC has more of a role in emotional and affective processes.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies [21,22] have used EEG signals to deal with such factors as risk and feedback, which affect human trust and decision-making, and support the results of this research. Using EEG signals recorded through a competitive decision-making game, Cohen [23] found that increased feedback processing lowers the power delta and theta waves, and increases the power of alpha and beta waves.…”
Section: Discussionsupporting
confidence: 80%
“…risk averse vs. risk-seeking) may vary on a participant-to-participant basis, and this emphasis may also change over time (e.g. due to response feedback; examples for such history-dependence are the hot-hand fallacy and the gambler's fallacy [28,34]). We assume that the importance of attributes is reflected in the amount of attention directed to them, which is in our paradigm the number of times an attribute is being fixated.…”
Section: Relative Alternative Values Based On Differences Between Attmentioning
confidence: 99%
“…We were also interested to know whether the winning/losing history of previous trials has an impact on the strategy deployed in the current trial. This could be due to reasons like hot-hand fallacy or gambler's fallacy [34]. We therefore developed in section 2.4 a variation of Prospect Theory in which the reward history modifies all model parameters taking into account interdependencies between trial outcomes, the latent variable model.…”
Section: Weak Correlation Between Trialsmentioning
confidence: 99%